Role of Penicillium chrysogenum XJ-1 in the Detoxification and Bioremediation of Cadmium - Xu, Xingjian; Xia, Lu; Zhu, Wei; Zhang, Zheyi; Huang, Qiaoyun; Chen, Wenli (Frontiers in Microbiology, 2015)
Microbial bioremediation is a promising technology to treat heavy metal-contaminated soils. However, the efficiency of filamentous fungi as bioremediation agents remains unknown, and the detoxification mechanism of heavy metals by filamentous fungi remains unclear. Therefore, in this study, we investigated the cell morphology and antioxidant systems of Penicillium chrysogenum XJ-1 in response to different Cd concentrations (0–10 mM) by using physico-chemical and biochemical methods. Cd in XJ-1 was mainly bound to the cell wall. The malondialdehyde (MDA) level in XJ-1 cells was increased by 14.82–94.67 times with the increase in Cd concentration. The activities of superoxide dismutase (SOD), glutathione reductase (GR), and glucose-6-phosphate dehydrogenase (G6PDH) peaked at 1 mM Cd, whereas that of catalase (CAT) peaked at 5 mM Cd. Cd exposure increased the glutathione/oxidized glutathione ratio and the activities of GR and G6PDH in XJ-1. These results suggested that the Cd detoxification mechanism of XJ-1 included biosorption, cellular sequestration, and antioxidant defense. The application of XJ-1 in Cd-polluted soils (5–50 mg kg−1) successfully reduced bioavailable Cd and increased the plant yield, indicating that this fungus was a promising candidate for in-situ bioremediation of Cd-polluted soil.